SISTEM PENGENDALIAN INTERNAL PENGGAJIAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN (STUDI PADA P.T. MANDALA MULTIFINANCE, Tbk BANDUNG) - Shinta Oktafien; Neng Bayyinah (Jurnal Manajemen Bisnis Performa, 2017)
This study aims to determine the effect of the payroll system on employee productivity at PT Mandala Multifinance, Tbk Bandung. The method used in this research is to collect quantitative data through questionnaires, observation, and documentation. While to know the data is to test the validity, reliability test spearman rank correlation coefficient, coefficient determination test, regression and hypothesis testing. Based on the results of internal control system of the variable relationship payroll on employee productivity, including the relationship between variables, but low-level connection. From the calculation results show that employee productivity is influenced by the internal control system of payroll by 13.7% while the remaining 86.3% is influenced by other variables not examined in this study such as communication, working motivation, leadership, and working  envirinment are suspected that effect employee productivity in addition to the internal control system of payroll under study. Based on the hypothesis test showed that the internal control system of payroll has a significant and positive effect on employee productivity in P.T. Mandala Multifinance, Tbk Bandung.